Language Learning Exposure and Grammatical Proficiency of Intermediate Pupils - Salas, Marz Kimberly T.; Legaspi, Ma. Judy B. (Philippine Social Science Journal, 2020)
The Philippines is recognized globally as one of the largest English-speaking nations. The majority of its population has at least some degree of fluency in the language. Filipinos are exposed to the heavy usage of English, not just in school but also in their everyday lives. Exposing elementary pupils to different language learning sources (home, friends, school, and media) can help them acquire the language more easily. Thus, the second-language acquisition is a holistic process, which means acquiring the second language is not confined within the four walls of the classroom. This paper describes the extent of language learning exposure and the level of grammatical proficiency of Grade 6 pupils of a Catholic school in Bacolod City. Similarly, it explores the difference in the pupils’ extent of language learning exposure and level of grammatical proficiency. Also, it determines the relationship between language learning exposure and grammatical proficiency.